SISTEM LAYANAN MONITORING KEGIATAN AKADEMIK SEKOLAH DENGAN MENGGUNAKAN PROGRESSIVE WEB APPS - Ammar , Andi Bau; Rahman; Syahbudin (Jurnal INSYPRO (Information System and Processing), 2024)
Abstract - Currently, education is an important foundation for building quality resources, which encourages all parties involved to keep abreast of increasingly rapid technological developments. In education, one of the benchmarks is the results of students' own academic activities; this can be known by assessing students' academic performance at school. This assessment process is important in education, but currently there are still many schools that still use manual methods to assess and monitor academic activities in schools. Assessing and monitoring school activities also requires data management, be it student data, teacher data, student schedules, or grades. This is also information that can be an important factor for parents, teachers, and students when carrying out the learning process and as material for evaluating the learning process. However, monitoring carried out manually has weaknesses, such as parents not being able to fully understand the learning process and academic activities of their children. By using technology, a system can be implemented that carries out the processes of storing data, managing data, and displaying data. This website-based school academic activity monitoring service system is a system created to develop and facilitate the process of assessing and monitoring school academic activities. Apart from providing semester grades to students, this system will also provide other academic information. System design was carried out using the Rapid Application Development (RAD) method based on Progressive Web Apps (PWA). This system can help parents, guardians, teachers, and students monitor academic activities at school. Keywords: monitoring, academic activity, rapid application development, progressive web apps.